ÐŸÑ€Ð¸Ð¼ÐµÐ½ÐµÐ½Ð¸Ðµ Ð°Ð½Ñ‚Ð°Ð³Ð¾Ð½Ð¸ÑÑ‚Ð¾Ð² ÐºÐ°Ð»ÑŒÑ†Ð¸Ñ Ð´Ð»Ñ Ð´Ð¾Ñ€Ð¾Ð´Ð¾Ð²Ð¾Ð¹ Ð¿Ð¾Ð´Ð³Ð¾Ñ‚Ð¾Ð²ÐºÐ¸ Ð±ÐµÑ€ÐµÐ¼ÐµÐ½Ð½Ñ‹Ñ… Ñ Ñ€Ð¸ÑÐºÐ¾Ð¼ Ñ€Ð°Ð·Ð²Ð¸Ñ‚Ð¸Ñ Ð´Ð¸ÑÐºÐ¾Ð¾Ñ€Ð´Ð¸Ð½Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ð¾Ð¹ Ð¸Ð»Ð¸ Ñ‡Ñ€ÐµÐ·Ð¼ÐµÑ€Ð½Ð¾ ÑÐ¸Ð»ÑŒÐ½Ð¾Ð¹ Ñ€Ð¾Ð´Ð¾Ð²Ð¾Ð¹ Ð´ÐµÑÑ‚ÐµÐ»ÑŒÐ½Ð¾ÑÑ‚Ð¸ - Kuzmina, O. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
For the antenatal preparation of pregnant women with the risk of development of excessively strong and dyscoordinated labor activity there was elaborated a therapeutic complex, oriented to the metabolic process activation in the mother–placenta–fetus system, as well as normalizing the production of steroid hormones, placental proteins and calcium ion concentration in blood. This is expedient to apply the calcium antagonists and Àctovegin preparation for pregnant women antenatal preparation.